Control of a high-order boost converter - Yeo, Jackie Shi Jing. (2012)
The purpose of this project is to design and implement three different analog low-order controllers to regulate the output voltage of the fifth-order boost converter. Two of these controllers are current mode based controllers. The last controller is voltage mode based controller. These controllers are designed to satisfy robustness and tracking capabilities criteria. Experimental results were provided to verify these criteria were met.